Debris flows in the Andean ranges of central Chile and Argentina triggered by 2013 summer storms: characteristics and consequences - Sepulveda, Sergio A. (2014)
In January and February 2013, heavy rainfall during local summer storms triggered a large number of landslides in the Andes Main and Frontal ranges of central Chile and Argentina (32°–34° S). Most of the mass movements classify as debris flows, while rockfalls and debris avalanches also occurred. The major debris flows occurred in the Maipo and Aconcagua valleys (Chile) and along the Mendoza River valley (Argentina). The debris flows caused serious disruption to the international highway connecting both countries and local roads and produced a large impact on the population of major cities downstream, mainly due to potable water supply cutoffs. Debris flow deposits have silt and clay particles usually ranging between 10 and 20 % by weight, which favors the movement of viscous flows in short, steep lateral gullies. Most of the flows tended to channelize, and the materials were deposited in alluvial fans and cones in areas with previous records of such events. This indicates that they constitute a significant hazard that may not have been properly considered in road infrastructure and potable water supply strategies for the region. This potential hazard may become more serious due to climate change in the near future.